Toward a framework for analyzing adaptive digital games' research effectiveness - Stefanie Vanbecelaere; Febe Demedts; Bert Reynvoet; Fien Depaepe (Serious Games Society, 2023)
Adaptive digital games for learning have been introduced as a motivating way for children to learn as they can provide instant feedback, embed the learning content in an attractive narrative, and adapt instruction according to individual needs of students. Although studies showed benefits of using adaptive digital educational games, a framework for analyzing research on the effectiveness of adaptive digital games is lacking. In this paper, we propose such a framework that accounts for a broad evaluation and is defined by (1) the learner variables that can affect effectiveness, (2) the adaptivity implemented in the tool, and (3) the learning outcomes being assessed . Next, this framework is used to describe recent intervention studies on the effectiveness of adaptive digital games in the context of K-12 education. We end with some concluding thoughts on the merits of such a framework for assessing the effectiveness of digital games and perspectives for future research.